Seasonal changes in N-cycling functional genes in sediments and their influencing factors in a typical eutrophic shallow lake, China - Zhang, Ling; Bai, Junhong; Zhai, Yujia; Zhang, Kegang; Wang, Yaqi; Tang, Ruoxuan; Xiao, Rong; Jorquera, Milko A. (Frontiers in Microbiology, 2024)
Abstract： N-cycling processes mediated by microorganisms are directly linked to the eutrophication of lakes and ecosystem health. Exploring the variation and influencing factors of N-cycling-related genes is of great significance for controlling the eutrophication of lakes. However, seasonal dynamics of genomic information encoding N-cycling in sediments of eutrophic lakes have not yet been clearly addressed. We collected sediments in the Baiyangdian (BYD) Lake in four seasons to explore the dynamic variation of N-cycling functional genes based on a shotgun metagenome sequencing approach and to reveal their key influencing factors. Our results showed that dissimilatory nitrate reduction (DNRA), assimilatory nitrate reduction (ANRA), and denitrification were the dominant N-cycling processes, and the abundance of nirS and amoC were higher than other functional genes by at least one order of magnitude. Functional genes, such as nirS, nirK and amoC, generally showed consistent decreasing trend from the warming season (i.e., spring, summer, fall) to the cold season (i.e., winter). A significantly higher abundance of nitrification functional genes (e.g., amoB, amoC and hao) in spring and denitrification functional genes (e.g., nirS, norC and nosZ) in fall were observed. N-cycling processes in four seasons were influenced by different environmental factors. Generally, dissolved organic carbon (DOC) or sediment organic matter (SOM), water temperature (T) and antibiotics (e.g., norfloxacin and ofloxacin) were significantly correlated with N-cycling processes. The findings imply that sediment organic carbon and antibiotics may be potentially key factors influencing N-cycling processes in lake ecosystems, which will provide a reference for nitrogen management in eutrophic lakes.